TRIBAL SELF-GOVERNANCE AND NATURAL RESOURCE MANAGEMENT IN SCHEDULE AREAS OF JHARKHAND: A CRITICAL ANALYSIS - Pandit , Sadanand (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
An institution of self-rule in the tribal village had been in existence since time immemorial. The system of tribal self-governance may be said to be as ancient as the tribals themselves. The village republic must have been formed by the tribal people for managing their village affairs and for maintaining their social solidarity. The Provisions of Part IX of the Constitution are extended to the Fifth Schedule Areas with certain modifications and exceptions by the PESA Act. The Gram Sabha manages the natural resources including land, forest and water in Schedule Areas in accordance with its tradition. However, this power is subject to the provisions of existing laws of land. Tribal peoples have emotional bonding with flora and fauna as most of the tribals are living in and around natural surroundings. They use natural resources as part of their survival while protecting these as part of their duties and obligations. The paper critically examines the function and power of tribal self-governance in fifth Schedule Area of Jharkhand. It also envisages the rights and privileges provided to the tribes under some legislations and how they manage natural resources in Jharkhand. To what extent the laws emphasize the rights and ownership of tribal people and respects their traditions in the control and management of resources.